ARE THOUGHT EXPERIMENTS GENUINE EXPERIMENTS? - Mettini, Guadalupe (Revista de Filosofía, 2024)
It has been argued that thought experiments are sufficiently similar to real experiments to claim that they constitute the same kind of practice, even though the lack of intervention in the material world deprives thought experiments their main source of objective knowledge. In this paper, I attempt to delineate the scope of this interpretation. I argue that perspectives that assert the equivalence of thought and real experimentation often use inappropriate analogies and fail to examine the specific characteristics of scientific experimentation. I argue that while these comparisons fall short, there are aspects in which thought experiments and real experiments share significant similarities that merit careful examination. To support this argument, I analyze a thought experiment proposed by Richard Feynman in 1965. I show that this experiment relies on a set of essential experimental skills developed through scientific training, relies on theoretical knowledge, and involves the ability to reconstruct causal chains.